Lipid content and cryotolerance of in vitro-produced bovine embryos treated with forskolin before vitrification - Meneghel, Melissa [UNESP]; Dall'Acqua, Priscila Chediek [UNESP]; Ambrogi, Marcela [UNESP]; Leão, Beatriz C.S. [UNESP]; Rocha-Frigoni, Nathália A.S. [UNESP]; Mingoti, Gisele Z. [UNESP] (FapUNIFESP (SciELO), 2017)
The aim of the present study was to evaluate the intracytoplasmic lipid content, development and cryotolerance of in vitro-produced bovine embryos treated with different concentrations of forskolin before vitrification. Embryos were produced from abattoir-derived ovaries and allocated into four groups. In the treatment groups, forskolin was added to the in vitro culture medium on Day 6 and incubated for 24 hours in one of the following concentrations: 2.5μM (Forsk 2.5 group), 5.0μM (Forsk 5.0 group) or 10.0μM (Forsk 10.0 group). Embryos from the control group were cultured without forskolin. On Day 7 of culture, the expanded blastocysts were stained with the lipophilic dye Sudan Black B for determination of the intracytoplasmic lipid content or were cryopreserved via the Vitri- -Ingá® procedure. Although there were no significant differences (P > 0.05) in the blastocyst rates between the Control group (44.9%) and the other treatments, the embryo production was lower (P < 0.05) in Forsk 10.0 group (38.8%) compared to Forsk 2.5 (50.5%) and Forsk 5.0 (54.7%) groups. The intracytoplasmic lipid content (expressed in arbitrary units of pixels) in blastocysts from the Control group (1.00±0.03) was similar (P > 0.05) to that found in Forsk 2.5 (0.92±0.03) and Forsk 10.0 groups (1.06±0.03) groups; however the lipid accumulation in blastocysts from Forsk 5.0 group (0.82±0.04) was lower than in the Control group (P < 0.05). Based on these results, Forsk 5.0 treatment was tested for cryotolerance and it was observed that the blastocoel re-expansion rate evaluated 24 hours after warming was greater (P < 0.05) in Forsk 5.0 group (72.2%) compared to the Control group (46.2%). In conclusion, pre-treatment with forskolin at a concentration of 5.0 μM for 24 hours before vitrification is effective in reducing the intracytoplasmic lipid content and, consequently, improves cryotolerance of IVP bovine embryos.
Keywords: Bovine; Cryotolerance; Embryo; Forskolin; In vitro production; Intracytoplasmic lipid accumulation; Lipid content; Vitrification